Commitment to Diversity: The Impact of Diversity and Inclusiveness on Athletic Department Organizational Attractiveness and Job Pursuit Intentions - Trevor Bopp; Andrew Goldsmith; Matthew B. Walker (Journal of Applied Sports Management, 2014)
Given the lack of minorities in intercollegiate athletics, it is important for athletic departments to enhance inclusion and diversity practices to better manage diversity. These efforts will ultimately make the organization more attractive for potential applicants. Research suggests a strong relationship between applicant perceptions of organizational attractiveness and job choice decisions. However, little work has been devoted to understanding whether an organization's commitment to diversity enhances these perceptions. The purpose of this study was to determine the impact of an athletic department's commitment to diversity on its perceived attractiveness and the job pursuit intentions of potential applicants. Participants (N = 160) were presented with recruitment brochures detailing an athletic department internship program. Each brochure contained identical information regarding the internship opportunity, but varied with regards to the references made to diversity and inclusion. Findings revealed significant differences between the brochures on organizational attractiveness as well as gender on job pursuit intentions, but not for other specific demographic factors. These results indicate the manner in which a commitment to diversity is framed will lead to enhanced perceptions of the organization and the greater likelihood of attracting potential applicants, regardless of race and gender.
Keywords: diversity; organizational attractiveness; job pursuit intentions